Strategic Management Cycle in Internalizing Student Discipline: A Qualitative Case Study in Adiwiyata Schools - Vira Nurohma Yalanyta; Achadi Budi Santosa; Dian Hidayati (Elementary Teacher Education Program, Majalengka University, 2026)
Every student should instill the value of discipline. This study aims to describe strategies for fostering discipline among students at the Adiwiyata school, Muhammadiyah Condongcatur Elementary School, using Hitt et al.'s strategic management cycle approach. This study employed a descriptive qualitative research method, supported by ATLAS.ti 9, for data analysis. The data analysis employed Miles, Huberman, and Saldana's model to ensure that the theoretical and practical results of this study could be understood and replicated in other schools to improve environmental discipline. In the results of this study, it was found that five stages are interrelated in a complete strategic management cycle, including: 1) strategy formulation (Strategize) through establishing visionary commitments, identifying challenges and obstacles and ecosystem synergy, 2) planning (Plan) is made structured by optimizing resource governance and policy legality, 3) implementation of the strategy (Act) is realized through habituation, role models, and integration of environmentally conscious learning, 4) supervision (Monitor) is carried out through direct observation of students' daily lives and periodic evaluations, until 5) results (Outcome) are achieved in the form of formal recognition of the predicate of an independent Adiwiyata school at the provincial level, manifestation of changes in student character to become a sustainable school culture.